Are boards on board? A model of corporate board influence on sustainability performance - Galbreath, Jeremy (eContent Management Pty Ltd, 2012)
Existing research on a board-of-director–sustainability performance relationship have largely examined inside directors, outside directors, and gender diversity – yet empirical results have yet to offer any definitive answers. I posit that this previous research lacks a thorough examination of the role of boards and the means and mechanisms by which they influence performance. Drawing on the board capital perspective and the role of boards, this paper develops a model that highlights the influence of board capital on the future sustainability performance of firms. The model takes into account specific types of human and social capital of outside directors which have previously been unexamined. Beyond the board capital perspective, an argument is put forth that values are largely neglected in the examination of boards of directors, but are necessary in the study of sustainability because of its normative implications. I therefore account for the value attunement concept as a moderating variable in the model. The paper draws on corporate governance and business ethics' literature to generate propositions and offer original insight into the drivers of sustainability performance in organizations.